Protease-activated receptor-2 ligands reveal orthosteric and allosteric mechanisms of receptor inhibition - Amanda J. Kennedy (Nature Portfolio, 2020)
Kennedy et al. report the pharmacological and in vivo profiling of two small molecule PAR2 inhibitors and an agonist. They conclude that while the small molecule agonist and one of the inhibitors bind to the orthosteric PAR2 binding site, the other inhibitor is a negative allosteric modulator, highlighting two distinct mechanisms of inhibition that could be targeted for future development of drugs that modulate PAR2.